Event‐triggered state estimation for stochastic hybrid systems with missing measurements. Issue 18 (2nd November 2018) - Jin, Zengwang; Hu, Yanyan; Sun, Changyin
Abstract : This study is concerned with the event‐triggered state estimation problem for a class of stochastic hybrid systems with missing measurements in a networked environment. Two independent Markov chains are introduced to, respectively, characterise the stochastic measurement missing and the possible modal (or mode) transition of the system. In consideration of the constrained bandwidth and limited power resources of networked systems, a closed‐loop event‐triggered mechanism based on the measurement innovation is designed to trigger data transmission only when trigger conditions are satisfied. To keep the exponentially increasing number of full hypothesis sequences in optimal estimation to bounded computational complexity, the interacting multiple model framework is extended to tackle event‐triggered sampling with the statistical information implicit in event‐triggered conditions sufficiently explored and the possible measurement missing taken into account. A Monte Carlo simulation involving tracking a two‐dimensional manoeuvring target with two operational modes is provided to demonstrate the effectiveness and efficiency of the proposed event‐triggered hybrid state estimation in the presence of missing measurements.